A Hybrid Review on Islamic Business Model Literatures: Implications for Government, SMEs and Future Research Studies - Najmudin Najmudin; Ahmad Fatoni; Suja'I Suja'I; Kurnia Dwi Sari Utami; Mohamad Ainun Najib (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to draw lessons from the Islamic Business Model literature through a Bibliometric and Systematic Literature Review. This study systematically examined a sample of 212 articles from the Scopus Q1 and Q2 databases to critically explore patterns of research development in the scope of Islamic business models from 1999 to 2025. The results of this study show that the current focus of Islamic business model research is on several elements, namely ethical governance and spiritual values, the development of Islamic business based on the Islamic financial system, Islamic entrepreneurship to achieve sustainable development, and finally Islamic marketing and Islamic branding in promoting the success of Islamic business. In developing elements of the Islamic business model, several elements that need to be targeted in future studies are the development of an integrated Islamic business model framework, evaluation of sharia social finance innovation, sustainable halal business digitalization strategies, integration of MSMEs in the global halal value chain, design of pro-sharia business ecosystem public policies, development of sharia-based business performance indicators, measurement of the social impact of Islamic fintech, Islamic fintech in supporting financial inclusion for disadvantaged groups, and data security and privacy protection in Islamic fintech.